AI-Supported Staff Development in Higher Education: A Systematic Literature Review of Digital Leadership and Responsible Governance - Efrita Norman; Enah Pahlawati; Adrian Adha (MES Management Journal, 2026)
Artificial intelligence is reshaping higher education by transforming teaching, assessment, knowledge management, administration, and professional work. However, its implications for staff development remain fragmented, particularly in relation to digital leadership and responsible governance. This systematic literature review synthesizes Scopus-indexed evidence on AI-supported staff development in higher education. Using a PRISMA-oriented review design, the study searched Scopus with the queryhuman resource management education AI. After applying publication year, document type, language, and relevance criteria, 28 studies were included and analyzed through thematic synthesis. The findings reveal three major themes. First, AI-supported staff development strengthens professional capability through employee growth, faculty well-being, assessment innovation, AI literacy, knowledge-service transformation, workforce readiness, and sociotechnical work design. Second, digital leadership and institutional readiness are essential for turning AI adoption into sustainable institutional capability through infrastructure, stakeholder participation, role-specific training, and inclusive digital culture. Third, responsible governance is critical to ensure ethical and human-centered implementation by addressing privacy, bias, transparency, academic integrity, accessibility, expert validation, psychological safety, and human oversight. This review contributes to the literature by reframing AI-supported staff development as a strategic human resource development agenda rather than a narrow technical training issue. It highlights that sustainable AI transformation in higher education requires alignment among staff capability, digital leadership, institutional readiness, and responsible governance.Keywords: AI-supported staff development; higher education; digital leadership; responsible AI governance; human resource development; AI literacy; human-centered AI